Shifting left for application security : bridging the divide between DevOps and security with the right security tools - Conrad, Peter (O'Reilly Media, Inc., 2022)
Security is a paramount concern for developers, operations and security engineers, and company CISOs alike. Security remains crucial from the earliest phases of application design and development through deployment and support. Rather than bolting on a few security tests at the end of the process, many teams today are shifting security left by using tools and processes to address security from the earliest phases of the pipeline. In this report, author Peter Conrad explains why "shifting left" is important and how you can apply this practice in your organization. Once you understand the challenges companies face under pressure to deliver applications faster and more securely, you'll be able to create security recommendations for your own organization--including strategies for making security a top priority for everyone.